Investigating coaches’ general beliefs on defining and identifying talent in basketball - Koopmann, Till; Chorengel, Arne; Schorer, Jörg (Frontiers in Psychology, 2025)
Coaches have various challenging tasks to handle, including athlete development and selection. Selection decisions are often based on the coach’s eye. That is, coaches use their experience and intuition to generate holistic and subjective evaluations of athletes as the basis for selection decisions. In this context, both general beliefs regarding talent (in sports) and sport-specific aspects play an important role. Research investigating coaches’ thought and decision-making processes underlying selection decisions is rare. Thus, the present study applied an online questionnaire with n = 125 basketball coaches to investigate coaches’ general beliefs regarding talent (in basketball). Findings show four themes. First, coaches believe talent (in basketball) is identifiable, multidimensional, and compensatory. That is, it is defined by the interplay of multiple characteristics that can compensate for each other within a holistic athlete profile. Second, coaches reported that not only the importance of players’ characteristics but also their own definition of talent (in basketball) change over time. Third, coaches show that both individual (e.g., anthropometry, technical skills) and environmental (e.g., family, training) factors are important for player selection. Fourth, coaches appear to include both objectively (e.g., lab-based tests) and subjectively (e.g., game observations) collected information within their decision-making, mainly relying upon the latter. In summary, this study highlights the continued importance of holistic, flexible, and developmental approaches to athlete evaluation. These findings should be included in reflective and evidence-informed coach development systems as coaches appear to remain the main decision-makers selecting athletes based on their coach’s eye.